Convenient method for detecting ski-turn features with inertial and plantar pressure sensors - Matsumura, S.; Ohta, K.; Yamamoto, S. I.; Koike, Y.; Kimura, T. (Proceedings, 2020)
Skiers need a convenient method that uses actual ski-turn data to determine their skill level quantitatively without impeding their movement. In this study, we propose a feature detection method designed to quantitatively assess the skill level involved in ski turns. Actual data were acquired from both expert and intermediate skiers while skiing by using a comfortable measurement system that uses compact inertial sensors attached to the user`s skis and waist, and plantar pressure sensors. The changes in body posture and the behavior of the skis were examined using acceleration and angular velocity (each on three axes) data output by the inertial sensors. The plantar pressure distributions generated during skiing were also examined. The results show that it is possible to detect the relationship between the behavior of the skis and the changes in body posture or the plantar pressure distribution, which allows the skier`s skill level to be quantitatively assessed.